Reward Loop ke Regulasi Diri: Realist Review tentang Mekanisme Impulsivitas Pemuda dalam Lanskap Video Pendek - Tomy Octavian (Jurnal Studi Pemuda, 2025)
The surge of short video consumption among youth has raised concerns about impulsivity and self-regulation. Previous studies have widely examined digital addiction and dopaminergic mechanisms, yet few have comprehensively integrated neuropsychological perspectives with algorithmic design and socio-cultural contexts. The novelty of this study lies in its use of a realist review framework to map the interaction between dopaminergic reward loops, digital impulsivity, and opportunities for self-regulation through a Context–Mechanism–Outcome (CMO) configuration. The main objective was to explain how reward loops operate in the adolescent brain, how they reinforce impulsivity, and under what conditions self-regulation can be activated amidst exposure to short-form video platforms. This study reviewed 42 articles across neuropsychology, developmental psychology, media studies, and youth research. Across 42 studies, the synthesized evidence indicates that algorithmically enhanced reward loops trigger high impulsivity, characterized by delay discounting, procrastination, and attentional deficits. However, neuroplasticity provides adaptive pathways for youth to develop self-regulation through mindfulness, episodic future thinking, and algorithmic literacy. The conceptual model produced illustrates the transition from reward loop to impulsivity and the adaptive shift toward self-regulation. This study contributes theoretically by bridging neuropsychology and youth studies within the digital media context, while its practical implications suggest the design of digital literacy programs grounded in self-regulation for young people.